Genome-Wide Expression Profile of Maize Root Response to Phosphorus Deficiency Revealed by Deep Sequencing - Shun-zhong SU; Ling WU; Dan LIU; Yan-li LU; Hai-jian LIN; Shu-zhi ZHANG; Ya-ou SHEN; Hai-lan LIU; Zhi-ming ZHANG; Ting-zhao RONG; Xiao ZHANG; Yue-hui TIAN; et al. (Journal of Integrative Agriculture, 2014)
Phosphorus (P) is one of the three primary macronutrients that are required in large amounts for plant growth and development. To better understand molecular mechanism of maize and identify relevant genes in response to phosphorus deficiency, we used Solexa/Illumina's digital gene expression (DGE) technology to investigate six genome-wide expression profiles of seedling roots of the low-P tolerant maize inbred line 178. DGE studies were conducted at 6, 24 and 72 h under both phosphorus deficient and sufficient conditions. Approximately 3.93 million raw reads for each sample were sequenced and 6 816 genes exhibited significant levels of differential expressions in at least one of three time points in response to P starvation. The number of genes with increased expression increased over time from 6 to 24 h, whereas genes with decreased expression were more abundant at 72 h, suggesting a gradual response process for P deficiency at different stages. Gene annotations illustrated that most of differentially expressed genes (DEGs) are involved in different cellular and molecular processes such as environmental adaptation and carbohydrate metabolism. The expression of some known genes identified in other plants, such as those involved in root architecture, P metabolism and transport were found to be altered at least two folds, indicating that the mechanisms of molecular and morphological adaptation to P starvation are conserved in plants. This study provides insight into the general molecular mechanisms underlying plant adaptation to low-P stress and thus may facilitate molecular breeding for improving P utilization in maize.